MEKANISME HUKUM DALAM POLA PERUSAHAAN INTI RAKYAT PERKEBUNAN - Ermanto Fahamsyah (Faculty of Law - Tarumanagara University, 2017)
PIR Plantations are implemented by mechanisms that have been determined in several laws and regulations. The mechanism is carried out in four phases, namely the preparation phase which includes project preparation; Phase of physical development, both gardens and settlements as well as various necessary infrastructure and facilities; The conversion phase, namely the phase of transfer of ownership of smallholdings and credit expenses to selected participating farmers; And post-conversion stage, which is the development stage that includes the repayment period of credit, farmers' development and farming towards the establishment of independent farmers. The Pattern of Core Company of Palm Oil Plantation is carried out by certain mechanism which has been regulated in the legislation and cooperation agreement. It is intended that the main purpose and objective in the implementation of the PIR Pattern of Oil Palm Plantation can be achieved as it should be, namely to create a mutually beneficial, sustainable, and sustainable relationship between the big plantation and the people's plantation. In addition, it discusses how to raise the living values of participating farmers and their families by increasing production and income of farming and to preserve natural resources. Although the mechanisms in the PIR Plantation Scheme have been regulated in legislation and cooperation agreements, the practice still finds problems. Primarily it is related to land rights mechanism, credit assistance to participants, extention to participant farmers, and sales of participant's palm fruit. The problems are caused by both legal and non-legal factors. Keywords: mechanisms, laws, company, nucleus, smallholders, estate